$\displaystyle a_{n} =\frac{1^{k} +2^{k} +...+n^{k}}{n^{k}} -\frac{n}{k+1} ,\ k\in \mathbb{N}$
$\displaystyle a_{n} =\frac{( k+1)\left( 1^{k} +2^{k} +\cdots +n^{k}\right) -n^{k+1}}{n^{k}( k+1)}$. Let $\displaystyle y_{n} =n^{k}( k+1) ,\ x_{n} =a_{n} y_{n}$
$\displaystyle y_{n}$ is strictly increasing and $\displaystyle \rightarrow \infty $ hence Stolz theorem conditions is applicable.
$\displaystyle \begin{array}{{>{\displaystyle}l}}
\frac{x_{n} -x_{n-1}}{y_{n} -y_{n-1}} =\frac{( k+1) n^{k} -n^{k+1} +( n-1)^{k+1}}{( k+1)\left( n^{k} -( n-1)^{k}\right)} =\frac{\frac{k+1}{n} -1+\left( 1-\…